KNOWLEDGE, ATTITUDE AND PERCEPTION OF RELATIVES TOWARDS AUTOPSY: A CROSS-SECTIONAL STUDY IN ODISHA (Journal of Forensic Medicine & Toxicology, 2022)
An autopsy is the gold standard investigation to know the cause of death. In developing countries, people are generally ignorant regarding the medicolegal values associated with autopsy. There are various myths and misconceptions regarding autopsy among the general population. Therefore, this present study was conducted to aware people of autopsy and its medical and legal value. A cross-sectional study was done at the mortuary of AIIMS, Bhubaneswar. It included 99 relatives satisfying the inclusion criteria. Data were collected using a questionnaire that was validated and approved through the institutional ethics committee and analyzed using SPSS Version 20. Out of the study population 23.23 %, 26.26%, 16.16%, and 20.20% were aware of the place, time, duration, and person involved in the autopsy respectively. The majority of the study population (97%) did not know the legal value of a post-mortem report. This was a significant finding that even without having the basic awareness about post-mortem examination almost all the participants cooperated in carrying out the necessities required for conduction of autopsy and timely completion of the autopsy. The knowledge and attitudes of relatives can thereby affect the outcome of a medicolegal case.
Keywords: Attitude; Autopsy; Knowledge; Perception; Inquest report; Death certificate